Solution 1.3:1d

From Förberedande kurs i matematik 1

Jump to: navigation, search

By using the power rules, we can rewrite the expression,

\displaystyle \left( \frac{2}{3} \right)^{-3} = \frac{2^{-3}}{3^{-3}} = \frac{\,\dfrac{1}{2^{3}}\,}{\,\dfrac{1}{3^{3}}\,} = \frac{\,\dfrac{1}{2^{3}}\cdot 3^{3}\,}{\,\dfrac{1}{\rlap{\,/}3^{3}}\cdot {}\rlap{\,/}3^{3}\,} = \frac{\,\dfrac{3^{3}}{2^{3}}\,}{1} = \frac{3^{3}}{2^{3}}\,,

and then carry out the calculation

\displaystyle \frac{3^{3}}{2^{3}} = \frac{3\cdot 3\cdot 3}{2\cdot 2\cdot 2} = \frac{27}{8}\,.